2023
DOI: 10.1038/s41398-023-02312-w
|View full text |Cite
|
Sign up to set email alerts
|

Cerebro-cerebellar functional neuroplasticity mediates the effect of electric field on electroconvulsive therapy outcomes

Abstract: Electroconvulsive therapy (ECT) is the most effective treatment for severe depression and works by applying an electric current through the brain. The applied current generates an electric field (E-field) and seizure activity, changing the brain’s functional organization. The E-field, which is determined by electrode placement (right unilateral or bitemporal) and pulse amplitude (600, 700, or 800 milliamperes), is associated with the ECT response. However, the neural mechanisms underlying the relationship betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 70 publications
2
1
0
Order By: Relevance
“…The previous studies found that extensive cerebellar‐cortex interactions underlie the cerebellum's regulation of movement, thought, and emotion 40,41 . Numerous studies have demonstrated that disruption of cerebellar‐cortex FC is one of the neurobiological changes in depression 42,43 and this abnormal cerebellar‐cortex FC can be ameliorated by ECT 44,45 . These findings collectively demonstrate that altered cerebellar‐brain resting‐state FC is strongly associated with ECT‐induced antidepressant effects, which is consistent with our findings that we found that increased FC between PCL and TP in MDD patients after ECT.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The previous studies found that extensive cerebellar‐cortex interactions underlie the cerebellum's regulation of movement, thought, and emotion 40,41 . Numerous studies have demonstrated that disruption of cerebellar‐cortex FC is one of the neurobiological changes in depression 42,43 and this abnormal cerebellar‐cortex FC can be ameliorated by ECT 44,45 . These findings collectively demonstrate that altered cerebellar‐brain resting‐state FC is strongly associated with ECT‐induced antidepressant effects, which is consistent with our findings that we found that increased FC between PCL and TP in MDD patients after ECT.…”
Section: Discussionsupporting
confidence: 92%
“…40,41 Numerous studies have demonstrated that disruption of cerebellar-cortex FC is one of the neurobiological changes in depression 42,43 and this abnormal cerebellar-cortex FC can be ameliorated by ECT. 44,45 These findings collectively demonstrate that altered cerebellar-brain resting-state FC is strongly associated with ECT-induced antidepressant effects, which is consistent with our findings that we found that increased FC between PCL and TP in MDD patients after ECT. The TP plays an important role in emotional processing, and TP lesions lead to emotional deficits.…”
Section: Discussionsupporting
confidence: 90%
“…Electroconvulsive Therapy (ECT) is a psychiatric treatment involving the delivery of electric currents (around 800-900 mA) through scalp electrodes. These currents pass through the skull and cerebrospinal fluid, generating a strong electric field throughout the brain, which induces seizures and reorganizes brain function [42,43]. ECT can lead to cognitive side effects, including attention, memory, and executive function impairments [44][45][46].…”
Section: Other Neuromodulation Methods (Ect Mst)mentioning
confidence: 99%